The Corporate Governance Landscape of Pakistan - Edited by Sadia Khan and Forward by Ishrat Husain (Karachi Oxford University Press, 2017)
This book provides a comprehensive guide to the existing policy frameworks, principles, and practices of corporate governance in Pakistan today
Include Bibliography and Index
Keywords: Corporate governance Pakistan -- Corporate governance -- Rules for Governance of Public Sector Enterprises